The perceived value of local knowledge tourism: dimension identification and scale development - Zhang, Hailin; Jiang, Jinbo; Zhu, Jinsheng (Jason) (Frontiers in Psychology, 2023)
Local knowledge tourism encompasses the rich cultural heritage, historical narratives, and traditional practices of a specific destination. Despite its significance in enhancing the tourist experience, there is a dearth of research examining the subjective perceptions and values of visitors engaging in local knowledge tourism. Consequently, there is a pressing need to explore the composition of perceived tourist values in this unique context. Employing a constructivist grounded theory approach, this study identifies and conceptualizes five distinct dimensions of perceived values in local knowledge tourism: functional value, emotional value, social value, cognitive value, and self-actualization value. Furthermore, an 18-item scale is developed to measure these dimensions quantitatively. This research makes several significant contributions: 1) it expands the scope of perceived value research within the tourism domain and enhances our understanding of the tourist experience in local knowledge tourism; 2) it provides a reliable instrument for future quantitative investigations into the behaviour and mindset of local knowledge tourists; and 3) it offers theoretical foundations and practical insights for destination managers seeking to develop tourism products tailored to the preferences and expectations of local knowledge tourists.